Minoxidil for treatment of resistant hypertension in chronic kidney disease: a retrospective cohort analysis - Mundt, Heiko; Lammert, Alexander; Krämer, Bernhard; Birck, Rainer; Benck, Urs Tobias (The journal of clinical hypertension, 2016)
Resistant hypertension is still a challenge and reserve antihypertensive agents are often necessary to achieve blood pressure control. One reserve antihypertensive is minoxidil, a direct vasodilator that is known for its strong blood pressure-lowering effect, but contemporary studies are sparse. The authors retrospectively analyzed 54 inpatients with uncontrolled hypertension despite the combined use of current antihypertensive agents. To investigate the effect of minoxidil when added to other antihypertensive agents, blood pressure was evaluated at the time minoxidil treatment was initiated and at discharge. Minoxidil treatment was associated with a significant reduction in blood pressure from 162.4±15.1/83.2±12.7 mm Hg to 135.8±12.2/72.8±6.9 mm Hg (P<.0001). This effect was sustained across all analyzed subgroups. Although the well-known adverse events of minoxidil limit its widespread use, these data show that minoxidil as a reserve antihypertensive agent still has a niche indication in the particular subgroup of patients with treatment-resistant or uncontrolled hypertension.